Sistem Informasi Kampus Politeknik Seruyan Berbasis Web untuk Mendukung Transformasi Digital Perguruan Tinggi - Hermansyah Hermansyah; Rabiatul Rabiatul (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Digital transformation in the higher education sector has become an important necessity in improving the quality of academic and administrative information services. Politeknik Seruyan, as a higher education institution, requires a web-based campus information system capable of providing fast, accurate, and integrated access to information for the entire academic community and the general public. This study aims to design and develop a web-based campus information system using the domain poltes.ac.id as the official campus information media. The website provides various important information including campus history, vision and mission, study programs, facilities and infrastructure, campus news, and other academic information services. The research method used is the Waterfall method consisting of requirements analysis, system design, implementation, testing, and maintenance stages. System implementation was carried out using the WordPress Content Management System (CMS) supported by a MySQL database and other web technologies to support website appearance and content management. The results of the study indicate that the developed campus information system is able to improve the effectiveness of information delivery, facilitate user access to data, and optimally support the digital transformation of higher education. The poltes.ac.id website also provides convenience for the public in obtaining official information related to Politeknik Seruyan online.